If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 4x + -4 Reorder the terms: 2(-1 + x) = 4x + -4 (-1 * 2 + x * 2) = 4x + -4 (-2 + 2x) = 4x + -4 Reorder the terms: -2 + 2x = -4 + 4x Solving -2 + 2x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 2x + -4x = -4 + 4x + -4x Combine like terms: 2x + -4x = -2x -2 + -2x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + -2x = -4 + 0 -2 + -2x = -4 Add '2' to each side of the equation. -2 + 2 + -2x = -4 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = -4 + 2 -2x = -4 + 2 Combine like terms: -4 + 2 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| 2x+2x-9=11 | | 4=5C-(-14) | | 5t-1=60-5 | | 1/2(-3)+5 | | -7/6x+5/4x=2 | | b+17=33 | | 4x-y=3y-7 | | -47+n=13 | | -6/-20 | | x^3-5x^2-23x-8=0 | | 5th-1=60-5 | | 1/j+1/n=1/u | | n+4/-16=-1 | | n-20=-1 | | 9c^2+6c-35=0 | | 5(3-x)+3x=6(2x) | | -7/4(5/4a+1)+7/6=-1561/1200+7/5a | | 5(2x+6)=-41-5-2x | | 5(3-x)+3x=12x | | 5/2=98-n | | 2=(4/3)-(5/z) | | 15-x+5=80 | | (3x^4/3)-7=41 | | (28x-4x^2)/(32x+12) | | 22-y=2 | | s^2-8s+2=0 | | 3x^4/3-7=41 | | a=-70+(-3b) | | 5/4/13/4=7/x | | 5-3(2-x)=0 | | 15x^2+20x-12=0 | | 3Q^2-34Q+24=0 |